2022
DOI: 10.1039/d1ta08469k
|View full text |Cite
|
Sign up to set email alerts
|

Silica: ubiquitous poison of metal oxide interfaces

Abstract: In this review, we consider electrochemical applications, broadly conceived, in which both ions and electrons play key roles in device operation and where exchange of oxygen between the gas and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 138 publications
1
15
0
Order By: Relevance
“…Through a systematic study of different additives, it was found that oxides described by Smith as basic, for example, lithia or calcia, resulted in an increased response rate, while those considered acidic, for example, silica or alumina, suppressed the response speed 18 . In line with the findings of Nicollet et al., the relaxation kinetics of PCO onto which Si‐species had been added to the surface responded considerably slower to stepwise oxygen changes than the pristine material, Figure 4B (blue) 3,18,27,43,44 . On the other hand, the basic additive lithia, resulted in an increased response rate, see Figure 4B (yellow).…”
Section: Case Studiessupporting
confidence: 75%
See 1 more Smart Citation
“…Through a systematic study of different additives, it was found that oxides described by Smith as basic, for example, lithia or calcia, resulted in an increased response rate, while those considered acidic, for example, silica or alumina, suppressed the response speed 18 . In line with the findings of Nicollet et al., the relaxation kinetics of PCO onto which Si‐species had been added to the surface responded considerably slower to stepwise oxygen changes than the pristine material, Figure 4B (blue) 3,18,27,43,44 . On the other hand, the basic additive lithia, resulted in an increased response rate, see Figure 4B (yellow).…”
Section: Case Studiessupporting
confidence: 75%
“…For example, Si‐species are recognized as an ubiquitous poison in metal oxide processing steps, for example, originating from furnace refractories and sealants/greases 3,27 . The widespread use of volatile organic silicon compounds (VSCs) in consumer products, for example, in electronics, furniture, healthcare, pharmaceuticals, cosmetics, and cookware, is already known to degrade SMOX‐based sensors 8,22,27 ; and therefore there is a significant push in the industry to develop stable sensor options 3,8 . Si‐species are known to significantly degrade SOFC cathode materials as well.…”
Section: Proposed Mechanisms For Surface Additive Influence On Intera...mentioning
confidence: 99%
“…Although many studies related to improving the initial performance of mixed conducting metal oxides have been pursued to date, particularly focused on tuning the oxygen exchange coefficient ( k chem ), the performance of such devices often degrades rapidly due to the inevitable poisoning by extrinsic sources over time during device operation. [ 8–11 ]…”
Section: Introductionmentioning
confidence: 99%
“…12,34,35 Electrolyte poisons reduce the ion transport capacity of the electrolyte to shut down the battery and prevent heat accumulation. 36,37 Thermal polymerization and thermal dedoping both involve chemical changes. Thermal polymerization inhibits ion transport within the electrolyte at high temperatures by self-polymerization to shut down the battery.…”
Section: Introductionmentioning
confidence: 99%